Efektivitas Program Bimbingan Perkawinan Pra Nikah dalam Mengurangi Angka Perceraian dengan Metode Root Cause Analysis - Nopilia, Leni; Kurnianto, Imam (JURNAL ILMIAH GEMA PERENCANA, 2022)
This research aims to analyze what is the cause roots of the increasing divorced rate caused by economy problems. The method use in this research is Root Cause Analysis (RCA). RCA is structure step by step technique that focused on find the cause of the problems and the solution rather than overcome the symptoms. This method good enough to help government understand the problems to achieve permanent solution. Applied RCA in this research is to inform what is happen (sourced from Badilag data where divorce rate is increasing): why did it happen (root of problems investigation analysis displayed in diagrams fishbone) and what is to be done to prevent something like that happening again (in the form of action plan).